Effectiveness, Safety and Tolerability of Vildagliptin with or without Metformin in Bangladeshi Patients with Type 2 Diabetes Mellitus: Results from Real-Life Observational Study - Latif, Zafar Ahmed; Pathan, Md Faruque; Uddin, Md Farid; Hasanat, MA; Ashrafuzzaman, SM; Ali, Tanvir Mobarak; Rahman, Md Mahfuzur (BIRDEM Medical Journal, 2016)
Background: Type 2 diabetes mellitus (T2DM) is a progressive disease which needs prolonged management with anti-diabetic drugs. The purpose of the present study was to assess effectiveness, safety and tolerability of treatment by vildagliptin alone or with the combination of vildagliptin and metformin in T2DM patients in a real-world setting. Methods: This non-interventional, prospective, multi-center study was conducted in several hospitals in Bangladesh from 15th September 2010 to 12th June 2012. Both male and female patients, aged ?18 years with an established diagnosis of T2DM, who had been prescribed vildagliptin or vildagliptin added to metformin free-dose or single-pill combination according to local prescribing information and who consented to data collection, were eligible for inclusion in the study. During the observational period of 24±6 weeks, data from three routine clinic visits were recorded; i.e. the baseline visit (Day 1), visit 2 (week 12±4 weeks) and a final visit (visit 3) at the end of the study (week 24±6 weeks). Result: A total number of 510 patients were enrolled in this study of which 468 patients were analyzed for the study and the remaining 42 patients were lost to follow up. Patients in vildagliptin group were treated with vildagliptin as monotherapy which was received by 101 patients; however, patients in vildagliptin/metformin group received the combination of vildagliptin and metformin which was in 367 cases. In vildagliptin group, the mean HbA1c was reduced from baseline (8.50±1.02 %) to 24 week (7.19±0.74%) (p<0.0001). Similarly, in vildagliptin group the mean HbA1c at week 12 (7.76±0.96 %) was lower vs. baseline (8.50±1.02 %) (p<0.0001). In vildagliptin and metformin combination group, the mean HbA1c at week 24 (7.02±0.66%) was lower vs. baseline (8.55±0.75%) (p<0.0001). There were no deaths and no serious adverse effects. None of the patients reported any hypoglycemic event. Conclusion: In conclusion vildagliptin treating T2DM patients with or without metformin is associated with a significant and clinically relevant improvement in glycaemic control. Furthermore, vildagliptin treatment is generally well tolerated Birdem Med J 2016; 6(1): 12-17